Effects of selected Palestinian plants on the in vitro exsheathment of the third stage larvae of gastrointestinal nematodes - Rana Majed Jamous; Mohammed Saleem Ali-Shtayeh; Salam Yousef Abu-Zaitoun; Alex Markovics; Hassan Azaizeh (BMC Veterinary Research, 2017)
Abstract Background Gastrointestinal parasites are one of the main restrictions to small ruminant production. Their pathological importance is primarily related to the major production losses, in quantity or quality, induced by the direct action of worms. Control of these parasites is based exclusively on the frequent use of anthelmintic drugs. However, the resistance to anthelmintics in worm populations after commercialisation of chemical drugs is now widespread. Therefore, there is a need to find new natural resources to ensure sustainable and effective treatment and control of these parasites. The aim of this study was to evaluate the anthelmintic activity, as minimum inhibitory concentration (IC 50 mg/mL), of different plant extracts using larval exsheathment inhibition assay using a two-species but steady population of parasitic nematodes (ca. 20% Teladorsagia circumcinta and 80% Trichostrongylus colubriformis). Results The study showed that the ethanolic extracts of 22 out of the 48 plant extracts, obtained from 46 plant species, have an inhibitory effect >50% (at concentrations of 100 mg/mL) on the third stage larvae (L3) of the nematodes exhibited the strongest inhibition activity (94%) with IC 50 of 0.02 mg/mL, where other members of the Rhamnaceae family have shown to possess strong anthelmintic activity (70–89%). Conclusions Plant extracts are potential rich resources of anthelmintics to combat helminthic diseases. Our results suggest that extracts from Rhamnus elaternus, Epilobium hirsutum, Leucaena leucocephala and Rhamnus palaestinus have promising anthelmintic activity, with potential applications in animal therapeutics and feed.